The effectiveness of Dionaea muniscipula's (Venua Flytrap) extract as a possible antibiotic - Pineda, Pamela Andrea L.; Bangud, Jerome A.; Hernandez, James Philippe M.; Alondra Rhoshell B.; Pagarigan, Jade L. (b)
Antibiotic resistance is a worldwide problem that has been ongoing for years. Researchers are continuously looking for new sources of antibiotics to help with this growing problem. Recently, it has been discovered that the Dionaea muscipula, more commonly known as the Venus Flytrap, is composed of phytochemicals that have the potential to exhibit antibacterial activities such as blumbagin, phenolic acid, flavonoids and their derivatives as well. This research focused on the possibility of Dionaea muscipula being an antibiotic. In order to perform the experiment, the plant was blended and macerated with 95% ethyl alcohol for 48 hours. The collected crude extract was then reduced to the following concentrations with distilled water; 70%, 50%, and 30%. With this, the bacterial samples were prepared using a streaking method wherein the plant extract was applied based on the concentration, which then were placed in a 37{mllhring}C incubator to facilitate the growth of the bacteria. For the antibiotic susceptibility testing, the Kirby-Bauer method was used and it yielded positive results. The extract of Dionaea muscipula and its reduced concentrations was proven to be effective in inhibiting the growth of the sample bacteria, namely; Staphylococcus spp., Vibrio spp., Salmonella sp. And Pseudomonas spp., and was even compared with the control antibiotics, erythromycin and cefuroxime. The zone of inhibition exhibited by the extract, along with its reduced concentrations in the bacteria are; (a) Staphylococcus spp.: 7 to 33 millimeters, (b) Vibrio spp.: 13 to 40 millimeters, (c) Salmonella sp.: 14 to 44 millimeters, and, (d) Pseudomonas spp.: 10 to 39 millimeters. The results, with the use of Two-way ANOVA and Turkey-Kramer test, showed that there is a significant difference between the varying treatments/concentration meaning that there is a visible difference in the effect as there is an increase and decrease on the inhibition of the bacterial samples based on the concentration of the Dionaea muscipula extract. Meanwhile, there is no significant difference regarding the effectiveness of the extract amongst the 4 bacterial samples, which indicated that the extract was equally effective to all the bacterial samples. In conclusion, the Dionaea muscipula extract is effective as an antibiotic and can even be compared to the effect of erythromycin and cefuroxime. It has the potential to be converted into medicine in the near future with the help of further studies.
Undergraduate thesis.
Keywords: phenolic acids; zone of inhibition; phytochemicals; Vibrio cholerae; Pseudomonas aeruginosa; Staphylococcus aureus; ethanol crude extraction; antibiotic resistance